Contingent variables to the price charged by hotels - Machado, M. J. (2019)
This study has two specific objectives: to analyse the association between the hotel features and the price charged; to analyse whether the performance evaluation tools used are associated with the price charged by the hotels. Data collection began with a survey directed at the financial managers of 4 and 5 star hotels located in Portugal to collect information on the performance evaluation tools used, and on some hotel features. We obtained 241 completed questionnaires, and to meet the objectives proposed, we also collected the price charged by the responding hotels, using the online platform Booking.com. The results obtained help us to fill a knowledge gap identified in the literature review regarding the influence of the hotel’s operating conditions on the price charged, since it leads to the conclusion that hotel features and the performance evaluation tools used influence the price charged.